Effects of Scapular Kinetic-Chain Exercise on Muscle Activity in Overhead-Pitching Baseball Players - Ki-Jae SONG; Jin Ho YOON; Jae-Keun OH (Tehran University of Medical Sciences, 2020)
Background: We aimed to demonstrate the effect of 8 wk of scapular kinetic-chain exercise on muscle activity in collegiate baseball players diagnosed with scapular dyskinesis. Methods: The subjects were career baseball players with at least a 7-year career assigned into either a SICK (S; scapular malposition, I; inferior border prominence, C; coracoid process pain, K; scapular dyskinesis; n=7) group or a normal group (n=16), respectively. The groups were further divided into SICK-Dominant, SICK-Non-Dominant, Normal-Dominant, and Normal-Non-Dominant to examine the dominant and non-dominant deviation of each group. Twenty-three subjects finally recruited through the Sports Science Institute of Korea National Sport University, Seoul, Korea in Sep 2014. Subjects were only allowed drug treatment for acute injuries during matches or training, and matches, training, and diet were controlled by university dormitory life. Results: There was a significant increase in maximal muscular activation (MA) in elevation motion of Normal-Dominant upper trapezii (UT), mean MA of SICK-Dominant UT, and mean MA of SICK-Dominant lower trapezii (LT) (P<0.05). In depression motion, the mean MAs of SICK-Dominant, Normal-Dominant, and Normal-Non-Dominant UT were significantly increased (P<0.05). The maximal MA of Normal-Dominant LT was significantly increased (P=0.029), and the SICK-Dominant and Normal-Dominant groups showed significantly higher maximal and mean MAs after exercise compared with the Normal-Non-Dominant group (P<0.05). The maximal MA of SICK-Dominant musculi serratus anterior was significantly lower than Normal-Dominant at pre-test (P=0.034), and the mean MA of SICK-Dominant musculi serratus anterior differed from Normal-Dominant and Normal-Non-Dominant (P<0.05) before testing, but only from Normal-Non-Dominant after testing (P=0.031). Conclusion: Scapular kinetic-chain exercise improved muscle activation in both overhead-pitching players with scapular dyskinesis and normal players.